2022
DOI: 10.1039/d2sc02745c
|View full text |Cite
|
Sign up to set email alerts
|

Simple yttrium salts as highly active and controlled catalysts for the atom-efficient synthesis of high molecular weight polyesters

Abstract: Two simple yttrium salts, YCl3THF3.5 and YCl3·6H2O, are highly active and controlled catalysts for the perfectly alternating ring-opening copolymerization of epoxides and cyclic anhydrides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(25 citation statements)
references
References 52 publications
0
25
0
Order By: Relevance
“…Because the YCl 3 •6H 2 O/[PPN]Cl turn-over frequency (TOF) of CHO/CPMA polymerization (TOF = 204 h −1 ) is greater than BO/CPMA (TOF = 152 h −1 ), 23 it was hypothesized that an equal volume mixture of BO/CHO would give a polymer with more CHO/CPMA repeat units. Gratifyingly, when CPMA was polymerized with an equal volume mixture of CHO/BO ( f CHO : 0.54), the resulting polymer was 52% CHO/CPMA repeat units and 48% BO/CPMA repeat units (Table 2, entry 3).…”
Section: Papermentioning
confidence: 99%
See 1 more Smart Citation
“…Because the YCl 3 •6H 2 O/[PPN]Cl turn-over frequency (TOF) of CHO/CPMA polymerization (TOF = 204 h −1 ) is greater than BO/CPMA (TOF = 152 h −1 ), 23 it was hypothesized that an equal volume mixture of BO/CHO would give a polymer with more CHO/CPMA repeat units. Gratifyingly, when CPMA was polymerized with an equal volume mixture of CHO/BO ( f CHO : 0.54), the resulting polymer was 52% CHO/CPMA repeat units and 48% BO/CPMA repeat units (Table 2, entry 3).…”
Section: Papermentioning
confidence: 99%
“…Recently we have shown that simple yttrium salts (YCl 3 THF 3.5 and YCl 3 ·6H 2 O), in the presence of bis(triphenylphosphoranylidene)ammonium chloride ([PPN]Cl), are effective and controlled catalysts for the ROCOP of multiple epoxides and cyclic anhydrides. 23 Given the high activity for multiple monomer pairs, in addition to the simplicity of the YCl 3 ·6H 2 O/[PPN]Cl system, we sought to investigate the synthesis of block and/or random co-polyesters via ROCOP of multiple epoxides and anhydrides in one pot. Herein, we report the ROCOP of one-pot mixtures of epoxides and cyclic anhydrides, and how mechanistic knowledge can help predict copolymer sequence a priori in only certain instances.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, extremely high monomer loadings are needed to acquire high molecular weight polymers (>30 kDa). We have previously identified yttrium based catalysts are active for ROCOP of epoxides and cyclic anhydrides, in which the environment around the metal center can be tuned to impact the rate and control of polymerization [9,10] . Simple yttrium‐based chloride salts, such as YCl 3 (THF) 3.5 and YCl 3 ⋅ 6H 2 O, along with a cocatalyst, were highly active for the perfectly alternating copolymerization of ten epoxide/cyclic anhydride monomer pairs, while maintaining good molecular weight control and suppressed side reactions (Figure 2B).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously identified yttrium based catalysts are active for ROCOP of epoxides and cyclic anhydrides, in which the environment around the metal center can be tuned to impact the rate and control of polymerization. [9,10] Simple yttrium-based chloride salts, such as YCl 3 (THF) 3.5 and YCl 3 • 6H 2 O, along with a cocatalyst, were highly active for the perfectly alternating copolymerization of ten epoxide/cyclic anhydride monomer pairs, while maintaining good molecular weight control and suppressed side reactions (Figure 2B). [10] While both yttrium catalysts displayed record turnover frequencies (TOFs) for various monomer pairs, there were some challenges for each catalyst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation